Beyond the Basics: E-Marketing and Rebranding Strategies for MSME Advancement - Lia, Della Ayu Zonna; Siswanto, Ely; Wahyudi, Handri Dian (Jurnal Pengabdian Masyarakat, 2024)
Purpose: MSMEs often struggle to establish a strong brand identity due to inconsistent product naming within their offerings. This lack of brand cohesion can hinder customer recognition and engagement. Consequently, consumers may have difficulty associating various products with a single manufacturer. To address this challenge, e-marketing and rebranding strategies can be implemented to create a unified and memorable brand image. By effectively employing these tactics, MSMEs can enhance brand awareness and foster customer loyalty, ultimately expanding their market reach and driving business success. Method: This article examines the branding challenges faced by MSMEs and introduces e-marketing and rebranding as effective solutions. It analyzes common obstacles, explains the strategies, and highlights their benefits for MSME success. Practical Applications: 1) Improved brand awareness, 2) Increased brand engagement; 3) Building a strong brand identity: 4) Increase customer loyalty; 5) Diversify sales. Conclusion: This article emphasizes the significance of branding for MSMEs and proposes e-marketing and rebranding as effective strategies to address common challenges. By adopting these approaches, MSMEs can enhance brand awareness, foster customer engagement, and cultivate loyalty, ultimately solidifying their market presence.